2012
DOI: 10.1186/1476-9255-9-39
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 receptor blockade suppresses adaptive and innate inflammatory responses in experimental colitis

Abstract: BackgroundInterleukin-7 (IL-7) acts primarily on T cells to promote their differentiation, survival, and homeostasis. Under disease conditions, IL-7 mediates inflammation through several mechanisms and cell types. In humans, IL-7 and its receptor (IL-7R) are increased in diseases characterized by inflammation such as atherosclerosis, rheumatoid arthritis, psoriasis, multiple sclerosis, and inflammatory bowel disease. In mice, overexpression of IL-7 results in chronic colitis, and T-cell adoptive transfer studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…The IL-7/IL-7R system has been described to play a role in MS as well as in other autoimmune diseases such as type 1 diabetes, rheumatoid arthritis and inflammatory bowel disease 24,33,34 . There is compelling evidence from animal models of these diseases that blocking of the IL-7RA leads to an amelioration of the disease course by modulating inflammatory processes [22][23][24]33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IL-7/IL-7R system has been described to play a role in MS as well as in other autoimmune diseases such as type 1 diabetes, rheumatoid arthritis and inflammatory bowel disease 24,33,34 . There is compelling evidence from animal models of these diseases that blocking of the IL-7RA leads to an amelioration of the disease course by modulating inflammatory processes [22][23][24]33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence from animal models of these diseases that blocking of the IL-7RA leads to an amelioration of the disease course by modulating inflammatory processes [22][23][24]33,34 . .…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of both preclinical and clinical evidence suggests that raised expression levels of interleukin (IL)-7 and/or the IL-7 receptor (IL-7R) are associated with various disease states, including rheumatoid arthritis [1][2][3], juvenile idiopathic arthritis [4], spondyloarthritis [5], psoriasis [6], primary Sjögren's syndrome [7][8][9][10], colitis [11], type 1 diabetes [12,13] and multiple sclerosis [14,15]. Genome-wide association studies have also identified genetic variations in IL-7R as a risk factor for some autoimmune diseases [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…IL7 regulates T‐cell differentiation, survival, and homeostasis, which mediates inflammation upon binding to IL7R . Increased gene expression of IL7R and lnc‐IL7R are observed in many inflammatory conditions including atherosclerotic plaques in humans . Thus, the dysregulation of some of the above T‐cell receptor signaling pathways could contribute to worsened ischemic brain injury in smokers.…”
Section: Discussionmentioning
confidence: 99%